Simulation Analysis of Energy Inputs Required by Agricultural Machines to Perform Field Operations - Francesco Paciolla; Katarzyna Łyp-Wrońska; Tommaso Quartarella; Simone Pascuzzi (AgriEngineering)
The evaluation of direct energy inputs and the assessment of the carbon footprint of an agricultural tractor during the execution of an agricultural operation is a complex task. Methodological approaches such as field surveys and life cycle assessments can provide unreliable and non-repeatable results. This study exploits the use of numerical simulation to assess the fuel consumption of two agricultural tractors and their CO2 emissions during the execution of pesticide treatment and milling. The digital models of the Landini REX 4-120 GB and the Fendt 942 Vario were developed, starting from experimental data acquired during field tests in which the power required at the power take-off (PTO) by the respective operating machine was measured. Two custom working cycles, simulating the two agricultural operations, have been defined and simulated. The estimated fuel consumption was 7.8 L∙ha−1 and 23.2 L∙ha−1, respectively, for the Landini REX 4-120 GB during pesticide treatment and for the Fendt 942 Vario during milling. The corresponding direct energy inputs required for the two agricultural operations were equal to 300.3 MJ∙ha−1 and 893.2 MJ∙ha−1, respectively. The estimated carbon footprint was 26.5 kgCO2∙ha−1 and 68.4 kgCO2∙ha−1 for pesticide treatment and for milling, respectively. Moreover, considering the operational efficiency of the systems, an analysis of the available mechanical work supplied by the fuel was conducted.